E-commerce : - Laudon, Kenneth C. (Pearson, 2014)
This market-leading text for E-commerce emphasizes the three major driving forces behind E-commerce, technology change, business development, and social issues to provide a coherent conceptual framework for understanding the field. This edition features updates to the text, data, figures, and tables based on the latest marketing and business intelligence available from eMarketer, Pew Internet & American Life Project, Forrester Research, comScore, Gartner Research, and other industry sources. All opening, closing and Insight on cases are new or updated.